Realism in William James's Philosophy of Religion - Abbas Haj Zeinolabedini; Mohsen Javadi (پژوهشنامه فلسفه دین, 2015)
James's primary interest in religion was directed to practical consequences of religious belief in believer's real life. His general approach to justify the truth of religious belief is resorting to these same consequences. Due to this background and due to some of James's own statements regarding his theory of truth according to which he identifies the truth of a belief with its practical utility, some interpreters have interpreted him as a philosopher who attempted to present pragmatism as an alternative to realism in metaphysics, epistemology, and philosophy of religion. In this article, relying on the whole James's statements concerning his theory of truth and focusing on his views about religious experience, the incorrectness of that interpretation will be shown and it will be proved that James's theory of truth presupposes mind-independent realities and he doesn't reduce truth to utility; and his commitment to pragmatism in providing justification for religious belief is not incompatible with his commitment to religious realism, the view that there is some knowable mind-independent object for religious belief.